2015
DOI: 10.2298/saj150715004o
|View full text |Cite
|
Sign up to set email alerts
|

On the integrated continuum radio spectrum of supernova remnant W44 (G34.7-0.4): New insights from Planck

Abstract: In this paper, the integrated continuum radio spectrum of supernova remnant (SNR) W44 was analyzed up to 70 GHz, testing the different emission models that can be responsible for its particular shape. The observations by the Planck space telescope made possible to analyze the high frequency part of radio emission from SNRs. Although the quality of radio continuum spectrum (a high scatter of data points at same frequencies) prevents us to make definite conclusions, the possibility of spinning dust emission dete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
1
6
1
Order By: Relevance
“…Errors onAltenhoff et al (1970) flux values are not correctly reported in theTable 2byCastelletti et al (2007), as also noticed byOnić (2015). We included inFig.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Errors onAltenhoff et al (1970) flux values are not correctly reported in theTable 2byCastelletti et al (2007), as also noticed byOnić (2015). We included inFig.…”
mentioning
confidence: 85%
“…Recent observations were performed between 10 and 20 GHz with QUIJOTE (Génova-Santos et al 2016), providing intensity and polarization maps along the Galactic Plane (24 • < l < 45 • , |b| < 8 • ), with an angular resolution of ∼ 1 • . Moreover, Planck observations using the Low Frequency Instrument were performed between 30 and 70 GHz (Onić 2015, and references therein), but here again, the resolution cannot provide accurate maps of SNRs at these frequencies. Dedicated higher resolution observations are thus required to firmly address and disentangle models.…”
Section: Introductionmentioning
confidence: 99%
“…It is characterised by an active surface (which consists of 1008 aluminium panels and of 1116 electromechanical actuators under computer control) on the pri-mary mirror that corrects opto-mechanical deformations induced by gravity and temperature fluctuations, and improves spatial resolution at high frequencies (Prandoni et al 2017). SRT is presently equipped with three cryogenic dualpolarisation receivers placed at different focal positions (Valente et al 2010, Navarrini et al 2016, Valente et al 2016, Navarrini et al 2017): a 7-beam K-band receiver (18−26.5 GHz, Gregorian focus), a mono-feed C-band receiver (5.7−7.7 GHz, Beam Wave Guide focal position), and a coaxial dual-feed L/P band receiver (0.305−0.41 GHz and 1.3−1.8 GHz, primary focus). A detailed description of the K−band multi-beam receiver is given in Orfei et al (2010).…”
Section: The K-band Setup With Srtmentioning
confidence: 99%
“…On the contrary, using new Parkes 64-m telescope observations, Cruciani et al (2016) found that presently known integrated continuum data do not favor the presence of either this emission component nor thermal bremsstrahlung radiation. Finally, based on the new Planck's data, Onić (2015) proposed that the spinning dust mechanism can account for a significant excess emission at 30 GHz from the vicinity of SNR W44. Furthermore, Génova-Santos et al (2016) found a very compelling evidence for the spinning dust emission associated with W44.…”
Section: The Emission Modelsmentioning
confidence: 99%
“…Generally, verification of several theoretical models (e.g., non-linear particle acceleration in young SNRs, significant thermal bremsstrahlung emission from the SNRs expanding in the dense environment, models of dust emission linked to the SNRs, etc) rely, particularly on a good knowledge of the high-frequency part of the radio as well as the microwave continuum of SNRs (Reynolds & Ellison 1992;Scaife et al 2007;Onić et al 2012;Onić & Urošević 2015;Onić 2015;Génova-Santos et al 2016). The ground based radio-observations of SNRs at frequencies higher than around 10 GHz generally suffer from the transparency issues due to the existence of Earth's atmosphere.…”
Section: Introductionmentioning
confidence: 99%